Exploring eco-industrial development in the global south: recognizing informal waste-picking as urban-industrial symbiosis? - Tröger, Danny (2023)
Industrial ecology (IE) is discussed as a suitable approach to resolve three widespread socio-ecological problems in the so-called global south: waste accumulation, unemployment, and lack of adequate housing. As the IE framework was developed mainly in the global north, its applicability in the global south is uncertain. The issue is discussed along the use of municipal waste as building materials as a concrete application of circular economy (CE) and IE principles, which could contribute to the alleviation of the aforementioned social-ecological problems. The study focuses on San Martin, a district in the Buenos Aires metropolitan areawhich suffers from these problems dispite its industrial capacities. A SWOT analysis that includes all PESTLE dimensions was applied to identify risks for the success of an IE-based strategy, including the main actors and stakeholders of local waste management. Key issues include the informality and low agency of non-profit organizations, fluctuations in the national economy, inefficiencies in waste collection and recovery, and a lack of awareness and policies on waste separation. One major challenge is the undervaluation of the relevance, expertise and efficiency of waste sorting and processing by informal waste pickers and non-profit organizations. These practices should be recognized as a symbiosis of the urban with the industrial metabolism. This way, the epistemic basis for the eco-industrial development (EID) framework can be layed to make it capable to empower them rather than further displace the people involved. In this way, urban EID could become a useful strategy to channel different scientific disciplines, knowledge and actors, knowledge and actors towards sustainable development.